Docetaxel-Loaded Nanoparticles Assembled from β-Cyclodextrin/Calixarene Giant Surfactants: Physicochemical Properties and Cytotoxic Effect in Prostate Cancer and Glioblastoma Cells - Gallego-Yerga, Laura; Posadas, Inmaculada; de la Torre, Cristina; Ruiz-Almansa, Jesús; Sansone, Francesco; Ortiz Mellet, Carmen; Casnati, Alessandro; García Fernández, José M.; Ceña, Valentín (Frontiers in Pharmacology, 2017)
Giant amphiphiles encompassing a hydrophilic β-cyclodextrin (βCD) component and a hydrophobic calix[4]arene (CA4) module undergo self-assembly in aqueous media to afford core-shell nanospheres or nanocapsules, depending on the nanoprecipitation protocol, with high docetaxel (DTX) loading capacity. The blank and loaded nanoparticles have been fully characterized by dynamic light scattering (DLS), ζ-potential measurements and cryo-transmission electron microscopy (cryo-TEM). The data are compatible with the distribution of the drug between the nanoparticle core and the shell, where it is probably anchored by inclusion of the DTX aromatic moieties in βCD cavities. Indeed, the release kinetics profiles evidenced an initial fast release of the drug, which likely accounts for the fraction hosted on the surface, followed by a slow and sustained release rate, corresponding to diffusion of DTX in the core, which can be finely tuned by modification of the giant amphiphile chemical structure. The ability of the docetaxel-loaded nanoparticles to induce cellular death in different prostate (human LnCap and PC3) and glioblastoma (human U87 and rat C6) cells was also explored. Giant amphiphile-based DTX formulations surpassing or matching the antitumoral activity of the free DTX formulation were identified in all cases with no need to employ any organic co-solvent, thus overcoming the DTX water solubility problems. Moreover, the presence of the βCD shell at the surface of the assemblies is intended to impart stealth properties against serum proteins while permitting nanoparticle surface decoration by supramolecular approaches, paving the way for a new generation of molecularly well-defined antitumoral drug delivery systems with improved specificity and efficiency. Altogether, the results provide a proof of concept of the suitability of the approach based on βCD-CA4 giant amphiphiles to access DTX carriers with tunable properties.